2018
DOI: 10.2147/jpr.s154852
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Athens Insomnia Scale in chronic pain patients

Abstract: PurposeTo confirm the psychometric properties of the Athens Insomnia Scale (AIS) among Japanese chronic pain patients.Patients and methodsIn total, 144 outpatients were asked to complete questionnaires comprising the AIS and other study measures. According to the original article, the AIS has 2 versions: the AIS-8 (full version) and the AIS-5 (brief version). To validate the AIS-8 and AIS-5 among chronic pain patients, we confirmed: 1) factor structure by confirmatory factor analysis; 2) internal consistency b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 41 publications
4
45
0
10
Order By: Relevance
“…First, all the patients with advanced cancer were recruited in Iran using a convenience sampling method. Although patients were recruited in different oncology units, the results are not necessarily generalizable to other ethnicities, other disease groups, or early stage of cancer, especially since different AIS and ISI structures have been reported across different populations in previous studies (Chung et al, 2011;Enomoto et al, 2018;Fernandez-Mendoza et al, 2012;Gerber et al, 2016;Gómez-Benito et al, 2011). Second, the different early treatments may also contribute to different sleep performance among the patients with advanced cancer.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…First, all the patients with advanced cancer were recruited in Iran using a convenience sampling method. Although patients were recruited in different oncology units, the results are not necessarily generalizable to other ethnicities, other disease groups, or early stage of cancer, especially since different AIS and ISI structures have been reported across different populations in previous studies (Chung et al, 2011;Enomoto et al, 2018;Fernandez-Mendoza et al, 2012;Gerber et al, 2016;Gómez-Benito et al, 2011). Second, the different early treatments may also contribute to different sleep performance among the patients with advanced cancer.…”
Section: Discussionmentioning
confidence: 94%
“…More specifically, the CFA and Rasch analysis findings supported the unidimensional structure for both the AIS and ISI. Previous studies have reported different factorial structures for AIS (one or two factors) (Enomoto et al, 2018;Gómez-Benito et al, 2011) and ISI (one to three factors) (Chung et al, 2011;Fernandez-Mendoza et al, 2012;Gerber et al, 2016) across different populations (e.g., adolescents and people with chronic pain). However, the different findings in the factorial structures could be contributing to the different sample characteristics.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Three items assess consequences of insomnia for the next day: sense of wellbeing during the day, physical and mental functioning during the day, and sleepiness during the day. The AIS � 8 was defined as insomnia among individuals with chronic pain [33].…”
Section: Main Measuresmentioning
confidence: 99%
“…Оцінку сну проводили о 18:00 на другий день після перенесеного оперативного втручання шляхом оцінювання за Афінською шкалою інсомнії (AIS) [11,12]. Рівень болю оцінювали у спокої о 9-й ранку після першої післяопераційної ночі за допомогою візуальної аналогової шкали (ВАШ) з урахуванням максимального рівня болю за ніч [13].…”
Section: матеріали та методиunclassified